Peculiarities of breast cancer incidence according to Vitebsk Regional Clinical Oncological Dispenser - Masalkova, Yuliya Yu.; Beliaeva, Darya I. (Journal of the Belarusian State University. Ecology, 2022)
The results of statistical processing of data on the diagnostics of breast cancer in patients of the Vitebsk Regional Clinical Oncological Dispensary for 2019-2020 are presented in this article. Extracts from medical records of 1061 patients (617 - 2019; 444 - 2020) aged 20 to 99 years were analyzed. In particular, methods for diagnosing the disease, the stages of registration of breast cancer were studied, the circumstances of the detection of the disease, the ratio of lesions of different parts of the mammary gland according to ICD-10, the results of the analysis of the occurrence of the disease depending on age, the features of the occurrence of relapses and metastases, the mortality of patients of different age groups, the ratio of patients from urban and rural areas. In 91.99 % of cases, the histological method was used to diagnose the disease. Echoscopic (0.75 % of cases) and X-ray (0.28 % of cases) diagnostic methods have found the least use. In the majority (45.80 % of cases) the disease was detected at stage II, in 7.71 % of cases breast cancer was registered at stage IV. In more than half of the cases (50.51 %), the disease affected the upper outer quadrant of the breast, which corresponds to the ICD-10 code C50.4 (Malignant neoplasm of the upper outer quadrant of the breast). There was an increase in the risk of breast cancer with increasing age of patients (approximation - 0.9577) with an average age of patients - 62 years. Relapses and metastases were found in 13.57 % of patients with breast cancer, and in 36.81 % of cases - at stage IV of the disease. Among patients, the largest number of relapses and metastases (22 cases each) was found in the age groups 55-59 and 60-64 years. Mortality for 2019-2020 was 7.92 % (84 patients died, among which relapses and metastases were detected in 38 people). Most of all patients (77.57 %) with diagnosed breast cancer live in urban areas, 22.43 % are patients from rural areas.